Remediation of Heavy Metals From Presco Campus Dumpsite Using Nano-Zero Valent Iron Supported Justicia Carnea Leaves Extract - Otu Mercy Oluchi; Nworie Felix Sunday; Otu Christian Glory (Andalasian International Journal of Applied Science, Engineering and Technology, 2026)
This study investigated the green synthesis of nano zero-valent iron supported Justicia carnea leaves extract and its application in remediating heavy metal contaminated dumpsite soil at PRESCO Campus, Ebonyi State University. UV-Vis spectroscopy revealed a strong absorption peak at 276 nm, confirming Fe0 formation, while FTIR analysis identified phytochemical functional groups responsible for reduction and stabilization. The untreated soils contained elevated levels of heavy metals including Cr, Mn, Fe, Co, Ni, Cu, Zn, and Pb. The synthesized nZVI showed appreciable remediation potential, with metal removal efficiencies varying across species and experimental conditions. Fe exhibited the highest uptake, reaching up to 92%, while Mn, Co, Cu, Zn, and Pb showed moderate to high removal. Adsorption was influenced by pH, temperature, contact time, and adsorbent concentration, with optimal removal observed at pH 7 and 39.85 C. Adsorption isotherms were described by both Langmuir and Freundlich models, indicating heterogeneous surface interactions. Kinetic evaluation revealed metal-specific behavior. Mn and partially Pb followed pseudo-second-order kinetics suggesting chemisorption, whereas Cr, Fe, Co, Cu, and Zn followed pseudo-first-order trends reflecting a combination of physisorption and chemisorption mechanisms. Overall, the findings show Justicia carnea mediated nZVI as a sustainable material for remediation of heavy metals in contaminated soils.